221k views
22 votes
Find the sum of 3a 2 + 4b 2 , 4a 2 – 3b 2 + 2ab and -4a2 + 2b 2 – 6ab​

1 Answer

4 votes

We have to find the sum of 3a² + 4b² , 4a² - 3b² + 2ab and - 4a² + 2b² - 6ab

Just add all these expressions and you will get your answer as ;


{:\implies \quad \sf (3a^(2)+4b^(2))+(4a^(2)-3b^(2)+2ab)+(-4a^(2)+2b^(2)-6ab)}


{:\implies \quad \sf 3a^(2)+4b^(2)+4a^(2)-3b^(2)+2ab-4a^(2)+2b^(2)-6ab}

Collect like terms ;


{:\implies \quad \sf (3a^(2)+4a^(2)-4a^(2))+(4b^(2)-3b^(2)+2b^(2))+(2ab-6ab)}


{:\implies \quad \bf \therefore \quad \underline{\underline{Required\: \: Sum=3a^(2)+3b^(2)-4ab}}}

User Mpowered
by
4.9k points